Combined Dystonia With Self‐Mutilation in 6‐Pyruvoyl‐Tetrahydropterin Synthase (PTPS) Deficiency: A Case Report. Issue 1 (8th November 2018) - Latorre, Anna; Salgado, Paula; Salari, Mehri; Jesuthasan, Aaron; Bhatia, Kailash P.
Abstract : View Supplementary Video 1